Synthesis and characteristic bioadditive of rubber seed oil as low pour point biodiesel CPO - . Misdawati; Muslih Nasution; . Syafiruddin (Syiah Kuala University, 2013)
The bigest point from CPO biodiesel is the high pour point, which is if used at low temperature will cause blockage the filter and fuel lines that make some problem in machine. To solve this problem was using pour point lowering additive, the widely used additive now was chemical commercial additive,which is have highest prices. Methyl ester that made form rubber seed oil have high free fatty acid needed two step reaction, esterification reaction to lowering the free fatty acid to £ 2% and transesterification reaction. The reaction variable was temperature, rubber seed oil/methanol ratio mol and concentrations ofKOH catalyst. Response Surface Methodology was used at transesterificstion reaction, first to know interaction variables effect in reaction, and seconded to get the optimum point. Optimum yield was obtained at 1/6 oil/methanol ratio mol, 1% concentration KOH catalyst and temperature 60°C with time reaction was 90 minutes. Reaction at the optimum condition obtains 99.61% conversion methyl ester (bioadditive) rubber seed oil.